2019
DOI: 10.1038/s41598-019-52774-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization and chemical validation of Leishmania MAP Kinase-3 as a potential drug target

Abstract: Protozoan parasites of the Leishmania genus have evolved unique signaling pathways that can sense various environmental changes and trigger stage differentiation for survival and host infectivity. MAP kinase (MAPK) plays a critical role in various cellular activities like cell differentiation, proliferation, stress regulation, and apoptosis. The Leishmania donovani MAPK3 (LdMAPK3) is involved in the regulation of flagella length and hence plays an important role in disease transmission. Here, we reported the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…On the other hand, Lmx MPK3 deletion mutants had a shorter flagellum ( Figure 2 ) [ 123 ], a similar phenotype to null mutants of Lmx MPKK1, the activating kinase of Lmx MPK3 [ 125 ]. Although Lmx MPK3 is not essential for parasite viability, small molecule inhibitors have been identified, as this kinase is important for Leishmania transmission [ 80 ]. Shweta Raj et al showed that the plant-based natural compounds genistein and chrysin ( Table 1 ) inhibited the kinase, and at the same time, minimized the parasitic load of infected macrophages ( Figure 2 ) [ 80 ].…”
Section: Mitogen-activated Protein Kinasesmentioning
confidence: 99%
“…On the other hand, Lmx MPK3 deletion mutants had a shorter flagellum ( Figure 2 ) [ 123 ], a similar phenotype to null mutants of Lmx MPKK1, the activating kinase of Lmx MPK3 [ 125 ]. Although Lmx MPK3 is not essential for parasite viability, small molecule inhibitors have been identified, as this kinase is important for Leishmania transmission [ 80 ]. Shweta Raj et al showed that the plant-based natural compounds genistein and chrysin ( Table 1 ) inhibited the kinase, and at the same time, minimized the parasitic load of infected macrophages ( Figure 2 ) [ 80 ].…”
Section: Mitogen-activated Protein Kinasesmentioning
confidence: 99%
“…Although MAPK-dependent pathways are one of the major cellular signaling cascades in mammals, it has scarcely been studied in Trypanosomatids. In a recent study, genistein (GEN) and chrysin (CHY) in a dose-dependent manner could inhibit the kinase activity of LdMAPK3 and thus exhibit anti-leishmanial activity ( Raj et al., 2019 ). In another study, LdMAPK1 was down-regulated in antimony-resistant clinical isolates, and susceptibility to antimony increased upon overexpression of LdMAPK1 in these parasites.…”
Section: The Regulated Cell Death Cascadementioning
confidence: 99%
“…LdBPK_363870.1 ( Figure 3 ) encodes a protein with similarity to mitogen-activated protein (MAP) kinases, a large family of enzymes implicated in antimony drug resistance (Ashutosh et al , 2012;Raj et al , 2019) . While candidacy was indicated by BS tests only in the East African population EA1, nucleotide diversity is also high in ISC1,2 and EA2 populations ( Supplementary Table 2 ).…”
Section: Genes Under Balancing Selection In the L Donovani Complexmentioning
confidence: 99%
“…LdBPK_363870.1 ( Figure 3 ) encodes a protein with similarity to mitogen-activated protein (MAP) kinases, a large family of enzymes implicated in antimony drug resistance (Ashutosh et al , 2012;Raj et al , 2019 and therefore an endomembrane member of the STE family (Baker et al , 2020) .…”
Section: Genes Under Balancing Selection In the L Donovani Complexmentioning
confidence: 99%